Pembuatan Silase sebagai Solusi Pakan Ternak pada Musim Kemarau di Desa Bonto Bulaeng Kabupaten Bantaeng: Making Silage as Livestock Feed Solution in the Dry Season in Bonto Bulaeng Village, Bantaeng Regency - Parawansya, Akram; Lestari, Rika Hari; Indriani, Indriani (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Bonto Bulaeng Village has a mostly hilly environment at an altitude of 500–800 meters above sea level. Because of its large and fertile area, Bonto Bulaeng Village has quite extensive land availability so it has enormous potential for the development of the livestock industry, one of which is cattle. The challenge faced by the community in community service activities through KKN is that during the dry season, it is difficult to provide forage for livestock. This activity aims to increase the community's understanding and skills regarding processing agricultural waste into silage for animal feed. The methods used in this activity include socialization and the practice of making silage by resource persons. The practice of making silage is the system carried out in this activity. Socialization is used to spread knowledge about silage, and the practice of preparing silage independently and through demonstrations is used to hone community skills. The results of this activity show that the community's knowledge and skills regarding silage-making increased significantly from 13.37% before the activity to 90.20% after the activity was carried out. These results indicate that the extension activities can be said to be successful because, after socialization, silage-making demonstrations, and independent practice, the community's knowledge and abilities are increasingly developing.